A Resisted Sprint Improves Rate of Force Development During a 20-m Sprint in Athletes. Issue 6 (June 2018) - Mangine, Gerald T.; Huet, Kevin; Williamson, Cassie; Bechke, Emily; Serafini, Paul; Bender, David; Hudy, John; Townsend, Jeremy
Abstract : Abstract: Mangine, GT, Huet, K, Williamson, C, Bechke, E, Serafini, P, Bender, D, Hudy, J, and Townsend, J. A resisted sprint improves rate of force development during a 20-m sprint in athletes. J Strength Cond Res 32(6): 1531–1537, 2018—This study examined the effect of a resisted sprint on 20-m sprinting kinetics. After a standardized warm-up, 23 (male = 10, female = 13) Division I basketball players completed 3 maximal 20-m sprint trials while tethered to a robotic resistance device. The first sprint (S1) used the minimal, necessary resistance (1 kg) to detect peak (PK) and average (AVG) sprinting power (P), velocity (V), and force (F); peak rate of force production (RFD) was also calculated. The second sprint (S2) was completed against a load equal to approximately 5% of the athlete's body mass. Minimal resistance (1 kg) was again used for the final sprint (S3). Approximately 4–9 minutes of rest was allotted between each sprint. Separate analyses of variance with repeated measures revealed significant ( p ⩽ 0.05) main effects for all sprinting kinetic measures except VPK ( p = 0.067). Compared with S1, increased ( p < 0.006) 20-m sprint time (3.4 ± 4.9%), PAVG (115.9 ± 33.2%), PPK (65.7 ± 23.7%), FAVG (134.1 ± 34.5%), FPK (65.3 ± 16.2%), and RFD (71.8 ± 22.2%) along with decreased ( p < 0.001) stride length (−21 ± 15.3%) and VAVG (−6.6 ± 4.6%) were observed during S2. During S3, only RFD was improved (5.2 ± 7.1%, p < 0.001) compared with S1. In conclusion, completing a short, resisted sprint with a load equating to 5% of body mass before a short sprint (∼20-meters) does not seem to affect sprinting time or kinetics. However, it does appear to enhance RFD.